2004
DOI: 10.1002/hep.20360
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of hepatocellular carcinoma cell growth by signal regulatory protein ?1

Abstract: Signal regulatory protein (SIRP) ␣1 is a member of the SIRP family that undergoes tyrosine phosphorylation and binds SHP-2 tyrosine phosphatase in response to various mitogens. The expression levels of SIRP␣1 were decreased in HCC tissues, compared with the matched normal tissues. Exogenous expression of wild type SIRP␣1, but not of a mutant SIRP␣1 lacking the tyrosine phosphorylation sites, in SIRP␣1-negative Huh7 human HCC cells resulted in suppression of tumor cell growth both in vitro and in vivo. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
(50 reference statements)
2
16
0
Order By: Relevance
“…The present data strongly support our previous findings and reports from other groups that SIRPa1 is one of the important binding partners of SHP-2 (Wu et al, 2000;Yan et al, 2004;Qin et al, 2006;Eminaga and Bennett, 2008). However, it is unclear how SIRPa1 modulates SHP-2 activity to exert its regulatory effects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present data strongly support our previous findings and reports from other groups that SIRPa1 is one of the important binding partners of SHP-2 (Wu et al, 2000;Yan et al, 2004;Qin et al, 2006;Eminaga and Bennett, 2008). However, it is unclear how SIRPa1 modulates SHP-2 activity to exert its regulatory effects.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study and reports from other groups have shown that SIRPa1 is involved in the regulation of cell migration and motility (Wu et al, 2000;Motegi et al, 2003;Yan et al, 2004). On the basis of these observations, we extended our study to assess the role of SIRPa1 receptor on tumor cell migration mediated by the constitutively active EGFRvIII oncoprotein.…”
Section: Sirpa1 Overexpression Downmodulates Egfrviiimediated Migratimentioning
confidence: 70%
“…Previously, decreased SIRP-α expression levels have been reported in various types of cancer, indicating its important role in oncology (9,10). The present study identified that SIRP-α expression tended to be lower in AIPC tissues compared with paired ADPC tissues.…”
Section: Introductionsupporting
confidence: 58%
“…SIRP-α has been shown to promote cell apoptosis in liver cancer (10) and breast carcinoma (9), but the molecular mechanism remains unclear. The present study confirmed that SIRP-α is involved in the regulation of cellular proliferation and apoptosis in ADPC and AIPC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SIRPs are expressed in neuronal cells (4 -6) and certain types of cancer cells (7)(8)(9)(10). SIRPs can be divided into two subfamilies, SIRP␣ and SIRP␤, based on the putative structures of their C-terminal intracellular domains (11).…”
mentioning
confidence: 99%